Personality maturation among emerging adults and future career success. Issue 2 (7th May 2019) - Kalfon Hakhmigari, Maor; Michaeli, Yossi; J. Dickson, Daniel; Scharf, Miri; Shulman, Shmuel
Abstract : Purpose: The purpose of this paper is to examine the role of maturation processes – personality change and reflectivity as characterized by greater awareness to self and others – during emerging adulthood in predicting career success. Design/methodology/approach: A sample of 205 of Israeli emerging adults was followed over a 12-year period. Participants completed measures of self-criticism at age 23 and 29, reflectivity at the age of 29 and subjective and objective career outcomes such as satisfaction with work and level of income at the age of 35. Hierarchical regressions determined the extent that decreases in self-criticism as well as greater reflectivity that predicted future career success. Findings: The findings of this paper indicated that greater decreases in self-criticism were longitudinally associated with less frequent negative experiences at work and lesser tendency to have doubts about one's career. Greater reflective capacity was longitudinally associated with a future higher income, greater career satisfaction and a stronger perception of one's career as a means to implement inner interests. Research limitations/implications: The results of this paper suggest that decreasing negative self-perception and enhancing awareness about self and others might facilitate a future career success. Originality/value: This is among the first studies that demonstrate the role of personality maturation during emerging adulthood for future career success.